Local fluid dynamics in patients with bifurcated coronary lesions undergoing percutaneous coronary interventions - Genuardi, Lorenzo (Cardiol J, 2021)
Although the coronary arteries are uniformly exposed to systemic cardiovascular risk factors, atherosclerosis development has a non-random distribution, which follows the local mechanical stresses including flow-related hemodynamic forces. Among these, wall shear stress plays an essential role and it represents the major flow-related factor affecting the distribution of atherosclerosis in coronary bifurcations. Furthermore, an emerging body of evidence suggests that hemodynamic factors such as low and oscillating wall shear stress may facilitate the development of in-stent restenosis and stent thrombosis after successful drug-eluting stent implantation. Drug-eluting stent implantation represents the gold standard for bifurcation interventions. In this specific setting of interventions on bifurcated lesions, the impact of fluid dynamics is expected to play a major role and constitutes substantial opportunity for future technical improvement. In the present review, available data is summarized regarding the role of local fluid dynamics in the clinical outcome of patients with bifurcated lesions.